PELATIHAN LITERASI KEUANGAN PRODUK DI KELURAHAN GUNUNG SULAH, KECAMATAN WAY HALIM, KOTA BANDAR LAMPUNG - Suripto Suripto; Supriyanto Supriyanto (Dharma: Jurnal Pengabdian Masyarakat, 2020)
The purpose of this service is to make Financial Literacy more attractive and can expand the product marketing reach for the people of Gunung Sulah Village. For the problems faced by the people of Mount Sulah, namely How to apply financial literacy in product activities. The long-term target to be achieved in this activity is closely related to the problem of developing financial literacy in the form of financial measurement which has a very wide reach, it is necessary to make efforts that lead to an increase in the amount of production and an increase in profits in terms of products seen from the physical quality, shape, taste. and colors, so that economic value can increase. The steps taken for this business are through fostering and increasing business development by choosing financial literacy to support businesses that can produce large amounts of production, short production time, increase production results and are of good quality. The output of this activity was a scientific article on Shinta 4 Lancang Kuning University, a video of the activity, and a profile of community service results published in a seminar on community service results from the University of Lampung. The method used is discussion, lecture and discussing interesting cases about financial literacy. By holding this training, it is hoped that it will make Financial Literacy more attractive and can expand the product marketing reach for the people of Gunung Sulah Village.